Differences in Perceptions Between Small Businesses and Large Businesses on Effectiveness of HR Management in Achieving Business Goal: Based on Field Evidence - Wibowo, Teguh Setiawan (Jurnal Ekonomi dan Bisnis Digital, 2024)
Human resources (HR) are a very important or key factor in the form of individuals or groups of people or workers as movers, thinkers and planners to achieve the business goals of a business. In business development to carry out greater expansion, a business's human resources function as assets that can be trained and developed in accordance with business interests in the business. HR management is tasked with recruiting, evaluating worker performance, ensuring that each person carries out their duties and responsibilities in accordance with their job, and maintaining worker satisfaction with their work environment so as to create effective conditions that support workers in increasing business profits for a business. However, the perception of the approach taken by HR management varies according to the size of the business, whether small or large. In this article, the difference in perception between small businesses such as Risol "Margo" and large businesses such as PT. Unilever's HR management effectiveness is based on 4 (four) factors, namely resource availability, recruitment and retention processes, employee responsibilities, and organizational structure which will influence both businesses in achieving their business goals.